Penerapan Buku Interaktif Sebagai Media Literasi Emosi Pengelolaan Rasa Khawatir Anak - Natasha (VisArt: Jurnal Seni Rupa dan Design, 2025)
Feelings of worry are a universal human experience, and this is no different for children. While a normal part of development, excessive and prolonged anxiety can become a significant threat to a child's mental well-being and development. Therefore, it is of foundational importance to provide emotional literacy from an early age, empowering children to recognize and manage their worries, which in turn can reduce the likelihood of developing more severe anxiety disorders later in life. This study aims to address this critical need by designing a children's book that effectively helps children cope with feelings of worry. The book’s core methodology is based on Cognitive Behavioral Therapy (CBT) techniques, which are adapted to be accessible and engaging for a young audience. To ensure the content is both psychologically sound and artistically effective, the research employs a descriptive qualitative method. This approach involves an extensive literature review to gain a deeper understanding of the depiction of worry, complemented by in-depth interviews with experts in the fields of child psychology and children's book illustration. The results of this comprehensive research were then systematically synthesized to form the evidence-based foundation for the book, titled “A Little Book About Big Worries.”